Proposed equity principles for transformative innovation, Through a critical analysis of agricultural innovation systems frameworks and tools - McGuire, Erin J.; Boa-Alvarado, Maria; Valencia Leñero, Eva Marina; Maha Al-Zu’bi, Maha; Thi Thu Giang Luu; Sylvester, Janelle M. (University of California, 2023)
The objective of this proposed scientific session aims to introduce the Equity Principles for Transformative Innovation (Equity Principles), which have been recently submitted to a Special Collection Supplement in Agricultural Systems. This session aims to help researchers understand the importance of inclusive Agricultural Innovation System (AIS) frameworks, and Agricultural Research for Development (AR4D) tools, and how to incorporate them into their work on socially effective and responsible innovation and scaling. The Equity Principles are a response to AIS frameworks and AR4D tools that consistently lack true integration of social differentiation or reflection on power and agency. The omission of these aspects often leads to unintended consequences and inequitable outcomes. Given the significant reliance on innovation and scaling in the AR4D community to achieve Sustainable Development Goals, it becomes crucial to consider the social aspects of these processes.